Clean Energy, Just Laws: Unpacking the Legal Backbone of SDG 7 in Indonesia - Yudys Zuama Pratama; Tajudeen Sani (Faculty of Law, Universitas Negeri Semarang, 2025)
The global pursuit of Sustainable Development Goal 7 (SDG 7) — ensuring access to affordable, reliable, sustainable, and modern energy for all — demands not only technological innovation and financial investment but also a robust legal and regulatory framework. This paper examines the critical role of law in advancing clean energy access in Indonesia, a country with abundant renewable energy potential yet facing complex socio-legal and infrastructural challenges. By analyzing national energy laws, regulatory policies, and international legal commitments, this research investigates how Indonesia’s legal system supports or hinders the realization of SDG 7. Special attention is given to the interplay between energy justice, environmental protection, and socio-economic equity in shaping the legal landscape. The study identifies key gaps in current legislation, such as the fragmentation of regulatory authority, the lack of legal incentives for renewable energy investment, and the limited enforcement of sustainability standards at the local level. It also highlights promising initiatives, including the Energy Transition Mechanism (ETM), green financing regulations, and community-based renewable energy projects. Through a legal-institutional analysis and stakeholder mapping, this research contributes to understanding how legal reforms can drive systemic change toward inclusive and sustainable energy governance. The findings offer a model for integrating legal design into national energy planning, emphasizing the importance of legal certainty, participatory governance, and policy coherence. Ultimately, this research provides actionable recommendations for strengthening Indonesia’s legal framework to unlock the full potential of clean energy and accelerate the achievement of SDG 7.